Building Union Muscle: The GoodLife Fitness Organizing and First-Contract Campaign - Savage, Larry (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
This case study of a union campaign to organize personal trainers and fitness instructors at GoodLife Fitness, the world’s fourth-largest fitness chain, is used to highlight the challenges and possibilities of organizing precarious workers in the multi-billion-dollar fitness industry. Drawing on the broader literature on union organizing and strategic corporate campaigns, primary documents related to the organizing drive, media coverage of the campaign, and in-depth interviews with union officials and fitness workers, the case study reveals how the workers were successfully, yet unconventionally, able to leverage institutional, symbolic, and associational power to build union muscle in an industry that is virtually union-free.